2008
DOI: 10.1128/jvi.00438-08
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Antiviral Protein Viperin Is Attenuated by Proteasome-Mediated Protein Degradation in Japanese Encephalitis Virus-Infected Cells

Abstract: Viperin is identified as an antiviral protein induced by interferon (IFN), viral infections, and pathogenassociated molecules. In this study, we found that viperin is highly induced at the RNA level by Japanese encephalitis virus (JEV) and Sindbis virus (SIN) and that viperin protein is degraded in JEV-infected cells through a proteasome-dependent mechanism. Promoter analysis revealed that SIN induces viperin expression in an IFN-dependent manner but that JEV by itself activates the viperin promoter through IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 54 publications
3
82
0
Order By: Relevance
“…Initial experiments showed that the stable ectopic expression of viperin inhibited HCMV assembly and maturation (7). Subsequent studies showed that the expression of viperin decreased the replication of HCV (20,24), Sindbis virus (6,63), and influenza viruses (60). Analogously, small interfering RNA (siRNA) knockdown of viperin reversed the poly(I ⅐ C)-induced inhibition of HIV replication (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial experiments showed that the stable ectopic expression of viperin inhibited HCMV assembly and maturation (7). Subsequent studies showed that the expression of viperin decreased the replication of HCV (20,24), Sindbis virus (6,63), and influenza viruses (60). Analogously, small interfering RNA (siRNA) knockdown of viperin reversed the poly(I ⅐ C)-induced inhibition of HIV replication (41).…”
Section: Discussionmentioning
confidence: 99%
“…Viperin (RSAD2 or cig5) is an ISG that is expressed in many cell types after exposure to type I and type II IFN, TLR agonists, or virus infection (7,23,41,51,64). Viperin localizes to the cytosolic face of the endoplasmic reticulum (ER) via its amphipathic ␣-helix (21,22), where it is believed to contribute to antiviral effects against hepatitis C virus (HCV) (20,24), Sindbis virus (6,63), HIV (41), influenza virus (60), and human cytomegalovirus (HCMV) (7) by modulating cholesterol and isoprenoid biosynthesis, lipid raft formation, and the composition and localization of lipid droplets (reviewed in reference 16). The ectopic expression of viperin additionally alters ER membrane morphology, which reduces bulk protein secretion and may affect the assembly and secretion of viruses that use an ER-derived exocytic pathway (22).…”
mentioning
confidence: 99%
“…Additionally, JEV NS4A protein is reported to block IFN action through inhibiting phosphorylation of Stat 1 and Stat 2 (Lin et al, 2008a). Moreover, aside from IFN antagonism at the level of Jak-Stat signalling, JEV is also able to inhibit a downstream antiviral molecule, viperin, by promoting its degradation via a proteasome-dependent mechanism (Chan et al, 2008).…”
Section: Type 1 Interferon Induction and Signallingmentioning
confidence: 99%
“…In mammals, viperin was characterized as one of IFN-inducible antiviral effectors (Carlton-Smith and Elliott, 2012;Fitzgerald, 2011;Helbig et al, 2011;Jiang et al, 2008;Mattijssen and Pruijn, 2012;Overby et al, 2009;Quraishi et al, 2010), and its expression regulation has been investigated in mammals (Boudinot et al, 2000;Chan et al, 2008;Chin and Cresswell, 2001;Olofsson et al, 2005;Saitoh et al, 2011;Severa et al, 2006;Stirnweiss et al, 2010). However, this information in fish is still unclear.…”
Section: Discussionmentioning
confidence: 99%